Efficacy of a Novel Nutritional Product in Acute Childhood Diarrhea in Guatemala: Secondary and Exploratory Analyses of a Randomized, Double Blind, Placebo Controlled Trial. (4th October 2017) - Gaensbauer, James; Melgar, Mario; Lamb, Molly; Calvimontes, Diva M; Asturias, Edwin J; Contreras-Roldan, Ingrid; Dominguez, Samuel; Robinson, Christine C; Berman, Stephen
Abstract: Background: PTM202 is a nutritional intervention for acute diarrhea that combines bovine colostrum with egg produced by hens vaccinated with USDA approved vaccines to standardize the levels of pathogen-specific immunoglobulin-Y, which target rotavirus, enterotoxigenic E. coli, shigatoxin + E. coli, and Salmonella. In a randomized, double-blind, placebo-controlled trial, PTM202 shortened acute non-bloody diarrhea in Guatemalan children who had ≥1targeted organism in stool. To further define the clinical relevance of these findings, we conducted secondary and exploratory analyses of study outcomes. Methods: From 3/2015 to 1/2016, 323 children 6–35 months with acute non-bloody diarrhea were randomized at three sites (1 rural, 2 urban) to one oral dose daily for 3 days of study product or placebo. Diarrheal pathogens on Day 1 were determined by multiplex PCR (FilmArray GI Panel, BioFire, USA). Product efficacy on diarrheal resolution (last diarrheal stool prior to formed or no stool in 12 hours) at days 1, 2, 3, and 7 after the initial dose, and 2 and 4 weeks weight recovery were assessed. Analyses were stratified by site and the presence of targeted organisms. Results: In urban patients with at least one targeted organism, statistically significant efficacy of the study product was noted at 1, 2, and 3 days (Table). No effect was demonstrated in analysis of all subjects, or in subjects with targeted organisms from the rural area (who had more targeted and non-targeted stool pathogens and poorer nutritional status). No impact of study treatment on 2 or 4 weeks weight gain was noted in overall or stratified analyses. Conclusion: PTM202 appears to shorten diarrheal duration in children with targeted stool pathogens, and may add to the therapeutic armamentarium against one of the major global causes of pediatric morbidity. Exploratory analysis suggests that three doses may not be required for efficacy – which would be a tremendous advantage for taking this treatment to scale in low and middle income countries – and will form the basis of future clinical trials. Disclosures: J. Gaensbauer, PanTheryx, Inc.: Grant Investigator and Investigator, Research grant. M. Melgar, PanTheryx, Inc.: Investigator, Research grant. M. Lamb, PanTheryx, Inc.: Investigator, Research grant. D. M. Calvimontes, PanTheryx, Inc.: Investigator, Research grant. E. J. Asturias, PanTheryx: Investigator, Research grant. I. Contreras-Roldan, PanTheryx: Investigator, Research grant. S. Dominguez, PanTheryx, Inc.: Investigator, Research support. S. Berman, PanTheryx: Investigator, Research grant